ENGAGING EFL JUNIOR HIGH SCHOOL STUDENTS IN MOVIE SUBTITLE MEDIATED FOR VOCABULARY LEARNING THROUGH VOCABULARY SELF-COLLECTION STRATEGY: A CASE SYUDY - Naufal Hisyam Ashshiddiq; Abdul Kodir Al-Baekani; Acep Bahrum Kamil (IKIP Siliwangi, 2024)
To communicate effectively in a foreign language, such as English, a person must first become familiar with the vocabulary in that language. A lack of vocabulary will make it difficult for students to express their understanding and even their production. In the EFL classroom, several media have the potential to help students learn vocabulary, one of which is films with subtitles. The study aimed To explore the extent of students’ involvement in the process of learning vocabulary through the use of movies with subtitles as a medium and to explore student’ perceptions towards the use of subtitled movie as a medium for vocabulary learning. The research method is qualitative using case study design. The participant were 5 high school students in Bekasi. The analysis data used thematic analysis by Braun and Clarke. Research showed that using films with subtitles greatly influenced on how students learned vocabulary. While interactive media aided understanding, clearer instructions were necessary for some. Students actively engaged in discussions, showing enthusiasm. However, the speed of subtitles posed a comprehension challenge. Enhancements in instructions and subtitle speed were crucial for effective learning.